Drivers of change in the Nordic Arctic: Compiled keywords from nine exploratory scenario exercises 2015-2020 - Nilsson, Annika E. (Luleå University of Technology, 2022)
This data set is a compilation of keywords and key phrases provided in brainstorming sessions from nine scenario exercises. They scenario exercises were based on a method to develop so-called extended shared socio-economic pathways in local participatory settings (for details, see Nilsson et al. 2017). The approach includes asking the participants an open question: What future changes may influence this region economically, environmentally, and socially within the perspective of one to two generations? The question guided an initial brainstorming session in nine participatory scenario exercises that were conducted between 2015 and 2020, covering various local contexts across the Nordic Arctic. These were held in Sweden: Pajala, 2015 (Nilsson et al. 2015) and Kiruna 2019 (Nilsson 2020); in Norway: Bodø 2015 (van Oort et al. 2015), 2020, and Alta, 2018; in Greenland: Ilulissat, 2018 and Narsaq 2019; and in Finland: Inari, 2015. In addition, one workshop was conducted in Kirovsk, Russia (2015) (van Oort et al. 2015).


Nilsson, A. E. (2020). Gruvor och hållbar utveckling i norra Sverige - går det att förena? Rapport från en workshop i Kiruna 6 november 2019 (No. RITA-ABE-RPT-207), Stockholm, Sweden: Avdelningen för historiska studier av teknik, vetenskap och miljö, KTH; https://www.rexsac.org/publications/gruvor-och-hallbar-utveckling-norra-sverige/

Nilsson, A. E., Bay-Larsen, I., Carlsen, H., van Oort, B., Bjorkan, M., Jylha, K., Klyuchnikova, E., Masloboev, V., van der Watt, L.-M., van der Watt, L.-M., Bjørkan, M., & Jylhä, K. (2017). Towards extended shared socioeconomic pathways: A combined participatory bottom-up and top-down methodology with results from the Barents region. In Global Environmental Change (Vol. 45, pp. 124–132). https://doi.org/10.1016/j.gloenvcha.2017.06.001

Nilsson, A. E., Carlsen, H., & van der Watt, L.-M. (2015). Uncertain futures: The changing global context of the European Arctic. Report from a scenario workshop in Pajala, Sweden, 9-10 March 2015 (SEI Working Paper No. 2015–12), Stockholm: Stockholm Environment Institute.

van Oort, B., Bjørkan, M., & Klyuchnikova, E. M. (2015). Future Narratives for Two Locations in the Barents Region (No. CICERO Report 2015:06), Oslo, Norway: CICERO Center for International Climate and Environmental Research - Oslo; http://hdl.handle.net/11250/2367371

Detta dataset är en sammanställning av nyckelord och fraser från nio scenarieövningar som bygger på en metod för att skapa "extended socioeconomic pathways" (för detaljerad beskrivning, se Nilsson et al 2017). I metoden ingår att ställa den öppna frågan: Vilka framtida förändringar kan komma att påverka regionen ekonomiskt, miljömässigt och socialt inom en eller två generationer? Frågan användes för ett inledande idéflöde vid nio olika scenarioövningar mellan 2015 och 2020 i olika lokala kontexter in nordiska Arktis. Övningarna hölls i Sverige: Pajala, 2015 (Nilsson et al. 2015) och Kiruna 2019 (Nilsson 2020); Norge: Bodø 2015 (van Oort et al. 2015), 2020, och Alta, 2018; Grönland: Ilulissat, 2018 och Narsaq 2019; och Finland: Inari, 2015. En workshop hölls i Kirovsk, Ryssland (2015) (van Oort et al. 2015).

Nilsson, A. E. (2020). Gruvor och hållbar utveckling i norra Sverige - går det att förena? Rapport från en workshop i Kiruna 6 november 2019 (No. RITA-ABE-RPT-207), Stockholm, Sweden: Avdelningen för historiska studier av teknik, vetenskap och miljö, KTH; https://www.rexsac.org/publications/gruvor-och-hallbar-utveckling-norra-sverige/

Nilsson, A. E., Bay-Larsen, I., Carlsen, H., van Oort, B., Bjorkan, M., Jylha, K., Klyuchnikova, E., Masloboev, V., van der Watt, L.-M., van der Watt, L.-M., Bjørkan, M., & Jylhä, K. (2017). Towards extended shared socioeconomic pathways: A combined participatory bottom-up and top-down methodology with results from the Barents region. In Global Environmental Change (Vol. 45, pp. 124–132). https://doi.org/10.1016/j.gloenvcha.2017.06.001

Nilsson, A. E., Carlsen, H., & van der Watt, L.-M. (2015). Uncertain futures: The changing global context of the European Arctic. Report from a scenario workshop in Pajala, Sweden, 9-10 March 2015 (SEI Working Paper No. 2015–12), Stockholm: Stockholm Environment Institute.

van Oort, B., Bjørkan, M., & Klyuchnikova, E. M. (2015). Future Narratives for Two Locations in the Barents Region (No. CICERO Report 2015:06), Oslo, Norway: CICERO Center for International Climate and Environmental Research - Oslo; http://hdl.handle.net/11250/2367371
Drivers of change in the Nordic Arctic: Compiled keywords from nine exploratory scenario exercises 2015-2020
Keywords: Arctic; Arktis; Kiruna; Kiruna; Ilulissat; Ilulissat; drivers of change; förändringsfaktorer; scenarios; framtidsscenarier; REXSAC; REXSAC; Social change; Social förändring; Other Social Sciences not elsewhere specified; Övrig annan samhällsvetenskap